Clonal and drug resistance dynamics of methicillin‐resistant Staphylococcus aureus in pediatric populations in China. Issue 2 (25th June 2019) - Yang, Xin; Liu, Yingchao; Wang, Lijuan; Qian, Suyun; Yao, Kaihu; Dong, Fang; Song, Wenqi; Xu, Hong; Zhen, Jinghui; Zhou, Wei
Abstract: Importance: Regional clonal replacements of methicillin‐resistant Staphylococcus aureus (MRSA) are common. It is necessary to understand the clonal and drug resistance changes in specific areas. Objective: To evaluate the clonal and drug resistance dynamics of MRSA in Chinese children from 2010 to 2017. Methods: MRSA was isolated from patients in Beijing Children's Hospital from 2010 to 2013 and from 2016 to 2017. The molecular characteristics and antibiotic resistance were determined. Results: In total, 211 MRSA isolates were collected, and 104 isolates were classified as community‐associated MRSA (CA‐MRSA). ST59‐SCC mec IV was the most prevalent type in both CA‐MRSA (65.4%) and healthcare‐ associated‐MRSA (HA‐MRSA) (46.7%). ST239‐SCC mec III accounted for 21.5% of all HA‐MRSA, which were not detected in 2016, and only three isolates were detected in 2017. The pvl gene carrying rate of CA‐ MRSA was significantly higher than that of HA‐MRSA (42.3% vs. 29.0%, P = 0.0456). Among CA‐MRSA, resistance rate to all tested antibiotics excluding chloramphenicol remained stable over the periods of 2010–2013 and 2016–2017. HA‐MRSA displayed an overall trend of decreased resistance to oxacillin, gentamicin, tetracycline, ciprofloxacin, and rifampin, and increased resistance to chloramphenicol, consistent with the difference of antibiotic resistance patterns between ST59‐SCC mec IV and ST239‐SCC mec III isolates. Vancomycin minimal inhibitory concentration (MIC) creep was found in the study period in all MRSA and ST59‐SCC mec IV isolates. Interpretation: ST59‐SCC mec IV has spread to hospitals and replaced the traditional ST239‐SCC mec III clone, accompanied by changes in drug resistance. Furthermore, vancomycin MIC creep indicated that the rational use of antibiotics should be seriously considered.